1972
DOI: 10.1017/s0003356100011375
|View full text |Cite
|
Sign up to set email alerts
|

The effect of condition at service and plane of nutrition in early pregnancy in the sow 1. Uterine and extra-uterine changes

Abstract: SUMMARYTwelve sows (F) were fed 7·3 kg/day and twelve (T) 3·7 kg/day of a 16% crude protein (CP) diet for the last 5 weeks of an 8-week lactation, so that at the subsequent service F sows were heavier (16%) and in better condition.From service to slaughter 70 days later, sows received either 3·7 kg/day (H) or 1·8 kg/day (L) of a 15% CP diet, giving four treatment combinations; FH, FL, TH and TL.In pregnancy H sows gained more weight than L sows and, on the low plane, F sows gained more weight than T sows. Ovul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, sows on the lowest plane of Elsley et al (1969) received more protein and energy than did the thin sows here. Some workers have reported an effect of body condition at mating (Hardy & Lodge, 1969;Pike & Boaz, 1972), and of the amount of feed given during the remating period on ovulation rate (Brooks & Cole, 1972a, b), and of the amount of feed during early pregnancy on embryo survival (Pike & Boaz, 1972). These would all tend to produce smaller litters, even though MacLean (1968) noted that litter sizes in herds with a thin sow problem ' appeared normal'.…”
Section: Discussionmentioning
confidence: 99%
“…However, sows on the lowest plane of Elsley et al (1969) received more protein and energy than did the thin sows here. Some workers have reported an effect of body condition at mating (Hardy & Lodge, 1969;Pike & Boaz, 1972), and of the amount of feed given during the remating period on ovulation rate (Brooks & Cole, 1972a, b), and of the amount of feed during early pregnancy on embryo survival (Pike & Boaz, 1972). These would all tend to produce smaller litters, even though MacLean (1968) noted that litter sizes in herds with a thin sow problem ' appeared normal'.…”
Section: Discussionmentioning
confidence: 99%
“…However, their results were not supported by a number of other reports, e.g. Hitchcock er at (1971), Pike & Boaz (1972), King et al (1982), Reese er al. (1982, King &Williams (1984a, b), andH ughes et al (1984).…”
Section: Lactation and Reproductionmentioning
confidence: 62%
“…In two studies the ovulation rate of sows was found to be correlated with body condition and with weight loss during lactation (Heap, Lodge and Lamming, 1967;Hardy and Lodge, 1969). In other studies no such relationship was established (Brooks, 1970;Pike and Boaz, 1972). The inability to establish a relationship does not preclude the possibility that body weight and/or condition are implicated in reproductive performance but merely indicates that under the conditions imposed they were not a limiting factor.…”
Section: Discussionmentioning
confidence: 92%